#TITLE_ALTERNATIVE# - RIKY (NIM 12103042), ANTON
Optimization is process turn out something more effective/complete, with proper adjustment for input. If optimization is process, then output of pit optimization is defined as pit effectively finished within highest profit (profit = revenue – cost). Mine planning can be explained with creating mine design that reach ultimate pit limit in a certain periode wit h benefit and safely. Inside also ultimate pit design, pushback, mine sequencing, production scheduling, etc (related with geometry). Another aspects include calculation of equipment and workers, operating and capital cost estimate. Mine Planning has aim in order to mine production planning for ore deposit that will deliver cash flow with maximizing economic criterion (NPV/ROR) at lower cost and fixed production capacity. This research has purpose to get optimal pit and knowing impact of revenue changes. For that, this final assignment using two software which NPV Scheduler and simple program (runs on fortran). This assignment will doing simulation of pit optimal, simulation of revenue changes eather decreasing or increasing revenue. The final assignment will be divided into two main parts. First, generates optimal pit (running NPV Scheduler fully), and for next work divide simulation into three scenarios (NPV Scheduler) and five scenarios (simple program) for simulation of revenue changes. The result of this research showing that pit optimization can generating optimal pit (especially economics view). Another result, showing the impact of revenue changes (especially decresing revenue) with consequently major changes in mine.